Activity of Cholpan in the literary environment of Bukhara - Shirinova, Mexrigiyo (FILOLOGIYA UFQLARI JURNALI, 2024)
The article expresses an opinion about Cholpon's activities in Bukhara. The author's work and writings in "Bukhara news" newspaper are analyzed. The fact that he was able to correctly assess the reality of Bukhara land, harmonizing it with world events, skillfully portraying it, and his attitude towards the people of art has been expressed. Key words: "Bukhara news" newspaper, Khoja Ismat Bukhari, Abdulkadir Savdo, "Yatimat-ut dahr" magazine, "Hablul matin", "Chehranoma", "Maintenance" newspapers, Sitorai Mohikhossa, Ark, Shirbudun.